Follistatin-Like 1 Is Downregulated in Morbidly and Super Obese Central-European Population. (22nd November 2018) - Horak, Martin; Kuruczova, Daniela; Zlamal, Filip; Tomandl, Josef; Bienertova-Vasku, Julie
Abstract : Follistatin-like 1 (FSTL1) is a secreted adipomyokine with a possible link to obesity; however, its connection to extreme obesity currently remains unknown. In order to analyze such association for the very first time, we employed a unique cohort of morbidly and super obese individuals with a mean BMI of 44.77 kg/m 2 and measured the levels of circulating FSTL1. We explored the 3 ′ UTR of FSTL1 to locate a genetic variant which impairs microRNA binding. We located and investigated such SNP (rs1057231) in relation to the FSTL1 protein level, obesity status, and other body composition parameters. We observed a significant decline in FSTL1 level in obese subjects in comparison to nonobese ones. The evaluated SNP was found to correlate with FSTL1 only in nonobese subjects. The presented results were not affected by sex since both males and females expressed FSTL1 equally. We suggest that the FSTL1 decrease observed in extremely obese subjects is a result of adipogenesis reduction accompanied by a senescence of preadipocytes which otherwise willingly express FSTL1, increased adipocyte apoptosis, and epigenetic FSTL1 silencing.